Measuring Cyberloafing in the New Normal Era: A General Approach - Harlina Nurtjahjanti; Rahmat Hidayat; Indrayanti Indrayanti (International Journal Labs, 2022)
The worldwide COVID-19 pandemic has altered the workplace and created the need to monitor employee performance in new ways to ensure the use of the internet remains productive during the new normal. Employees' engagement in the non-work-related use of the internet or cyberloafing in the new-normal era is interesting to discuss, where technology and information are developing so rapidly, increasingly blurring the line between work and non-work times. This paper investigates the literature related to recent advances in the concept of cyberloafing and discusses the need for developing new cyberloafing instruments. The research method used was a mini systematic literature review. The mini-review obtained thirteen articles meeting the criteria. In this paper, we also outline some recommendations for future research.